Educational visions The lessons from 40 years of innovation - Ferguson, Rebecca; Jones, Ann; Scanlon , Eileen (Ubiquity Press, 2019)
"Educational Visions looks to future developments in educational technology by reviewing its history, covering themes such as learning analytics and design, inquiry learning, citizen science, inclusion, and learning at scale. The book shows how successful innovations can be built over time, informs readers about current practice and demonstrates how they can use this work themselves. The chapters show how one research group has worked persistently over 40 years with four visions in mind, of a future where: • learning is accessible for everyone • teaching is adapted to meet learners' needs • teams can successfully teach any number of students at a distance • learners engage enthusiastically with STEM learning. Each vision is covered in a pair of chapters: the first brings together four decades of research in the area; the second introduces current work, showing how they are united by a consistent framework and a persistent vision."